2013
DOI: 10.1111/1365-2656.12137
|View full text |Cite
|
Sign up to set email alerts
|

Linking social and pathogen transmission networks using microbial genetics in giraffe (Giraffa camelopardalis)

Abstract: Summary 1.Although network analysis has drawn considerable attention as a promising tool for disease ecology, empirical research has been hindered by limitations in detecting the occurrence of pathogen transmission (who transmitted to whom) within social networks. 2. Using a novel approach, we utilize the genetics of a diverse microbe, Escherichia coli, to infer where direct or indirect transmission has occurred and use these data to construct transmission networks for a wild giraffe population (Giraffe camelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
249
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(257 citation statements)
references
References 66 publications
4
249
4
Order By: Relevance
“…In our parasite-sharing transmission networks, the meaning of an edge is not equivalent to networks constructed based on contact patterns. Whereas contact networks represent potential for transmission based on co-occurrence in space and time, we follow others [23,24] by assuming that edges in our transmission networks depict the potential for transmission between a pair of individuals of the same or different host species based on ecological and physiological characteristics that promote parasite sharing. By transmission potential, we mean the likelihood that a given individual will infect another individual, relative to other individuals in the network, based on observed parasite sharing.…”
Section: Network Centrality In Transmission Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…In our parasite-sharing transmission networks, the meaning of an edge is not equivalent to networks constructed based on contact patterns. Whereas contact networks represent potential for transmission based on co-occurrence in space and time, we follow others [23,24] by assuming that edges in our transmission networks depict the potential for transmission between a pair of individuals of the same or different host species based on ecological and physiological characteristics that promote parasite sharing. By transmission potential, we mean the likelihood that a given individual will infect another individual, relative to other individuals in the network, based on observed parasite sharing.…”
Section: Network Centrality In Transmission Networkmentioning
confidence: 99%
“…A third limitation is that TPNs may not represent true individual contacts. However, a recent study by VanderWaal et al [23] showed that a network based on shared E. coli strains co-varied with a network of social contacts in giraffes (Giraffa camelopardalis). This finding supports the assumption in our study (and in their later study on multi-host networks [24]) that transmission pathways based on shared parasites can reflect transmission pathways based on social contacts.…”
Section: The Use Of Transmission-potential Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of SNA to integrate individual behavior and population structure allows for a more sophisticated exploration of questions at both levels; many behaviors can only be fully understood when placed within the social context of the entire population. For example, the spread of social information, diseases, or parasites through a population depends not only on whom an individual directly interacts with, but also with whom their social partners interact (Godfrey et al, 2009;VanderWaal, Atwill, et al, 2014).…”
Section: Box 1 Terminology Of Social Network Analysismentioning
confidence: 99%